Exploring business opportunities at Panchor Dayak Hotspring Village / Nurfadzilla Mohd Fadzel - Mohd Fadzel, Nurfadzilla (2014)
A final year students of Bachelor Administrative Science (Hons), Faculty of Administrative Science and Policy Studies, Universiti Teknologi Mara (UiTM) are required to undergo the practical training. The students will be placed in the government or private organizations of their choice for a period of fifth weeks which is started from 21st July until 29th August 2014. During the practical training, the student also required to do a report. This training is very beneficial and important to expose students to the various aspects of industrial practises and ethics. The students are also able to apply the theories and knowledge that they have learned to the projects assigned to them. In this chapter would summarize on organizational background of the practical training place.